Escuela de padres: un modelo centrado en valores (2000)
This article is a study of an alternative model of Parents’ School.The background records, historical and social elements and some investigations from different Latin- American countries and from Colombia were examined to identify the schemes of work. Finally, the proposed model appears methodologically supported on partici¬pant research conceiving the family from the systems theory and the contents of the school from values development and life quality.